Multimodal imaging features of retroperitoneal anastomosing hemangioma: a case report and literature review - Zhang, Liqing; Wu, Jian (Frontiers in Oncology, 2023)
Background: Anastomotic hemangioma is a rare subtype of capillary hemangioma primarily found in the genitourinary tract. We present a case of a patient with an anastomotic hemangioma located in the retroperitoneal space, then we explore and summarize the imaging features from previously reported cases for accurately diagnosis.A 57-year-old woman complained of left lower back pain. Contrast-enhanced ultrasound revealed a hypoechoic mass with "slow-in and slow-out" enhancement. Abdominal CT scan displayed a well-defined, round soft tissue mass in the right retroperitoneal region with obvious enhancement. MRI indicated low signal on T1-weighted imaging, high signal on T2-weighted imaging and diffusion-weighted imaging, and progressive enhancement after enhancement. Surgical removal of the tumor was performed. Histopathological examination exhibited a distinct tumor border with interconnected blood vessels and a cavity lined by a single layer of cubic endothelial cells. Immunohistochemistry confirmed the presence of CD31[+] and CD34[+]. The final pathological diagnosis was anastomotic hemangioma. No recurrence was observed during a 40-month follow-up.Retroperitoneal anastomotic hemangioma is a rare and benign neoplasm that may be misdiagnosed as ectopic pheochromocytoma or angiosarcoma. This case report presents and analyzess the imaging characteristics of a series of retroperitoneal anastomotic hemangiomas, which can be valuable for future diagnoses and help prevent unnecessary surgeries.